Density functional investigation of relativistic effects on the structure and reactivity of tetrahedral gold clusters - De, Himadri Sekhar; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2009)
The influence of relativistic effects on the structure, vibrational modes, and reactivity of recently discovered tertrahedral gold clusters (Au(19) and Au(20)) are investigated using density functional methods. The intramolecular reactivity of the clusters was analyzed using density functional-based reactivity descriptors. The work shows that whereas the structural properties and vibrational modes are considerably affected by the relativistic effects, the reactivity trends based on Fukui function calculation on various atoms within this cluster remain unaffected by the absence or presence of relativistic effects. The reactivity descriptors reveal that the vertex atoms are the most reactive ones in Au(20) toward a nucleophilic attack. On the other hand, atoms connecting the missing vertex edge with the pyramid base along with the vertex atom are the most reactive for a nucleophilic attack in Au(19). The atoms lying at the center of each face are favorable for an electrophilic attack in both cases. Interestingly, the atoms with a missing cap in Aulg are highly favorable for electrophilic attack, and Au(20) has more sites for a favorable nucleophilic attack.

Understanding the reactivity properties of Au-n (6 <= n <= 13) clusters using density functional theory based reactivity descriptors - De, Himadri Sekhar; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2010)
{Relativistic density functional theory (DFT) based calculations have been performed on gold clusters with six to thirteen atoms (Au-n

Finite temperature behavior of gas phase neutral Au-n (3 <= n <= 10) clusters: a first principles investigation - De, Himadri Sekhar; Krishnamurty, Sailaja; Mishra, Deepti; Pal, Sourav (Journal of Physical Chemistry C, 2011)
{Relativistic density functional theory (DFT) based molecular dynamical simulations are performed on gold clusters with 3-10 atoms (Au-n

First principle investigation on the thermal stability of a golden fullerene: a case study of Au-32 - De, Himadri Sekhar; Krishnamurty, Sailaja; Pal, Sourav (Catalysis Today, 2012)
Structural and electronic properties of Au-32 cluster are analyzed using relativistic density functional theory (DFT) based methods. Further, DFT based molecular dynamical (MD) simulations are performed on Au-32 golden fullerene with an aim of understanding its thermal stability at various working temperatures. Various conformations being populated at different temperatures of a cluster are analyzed. The study shows that the ground state icosahedral conformation is stable only up to 300 K and structure remains in a hollow conformation only up to 400 K. This clearly explains the reasons for failure by experimentalists in trapping the unique fullerene conformation in spite of the theoretical predictions of it being a very stable one. The above MD study also indicates that the bare fullerene Au-32 cluster (without any stabilizing ligands) can be used for potential catalytic applications only around room temperatures. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Au-32 cluster; Born-Oppenheimer molecular dynamics; Density functional theory; Golden fullerenes; Relativistic effects